The dynamic effects of competition on investment: the case of the European mobile communications industry - Kalvin Bahia; Pau Castells (International Telecommunications Society (ITS), 2022)
We evaluate the impact of competition on investments in Europe's mobile communications market during the 2011-2021 period. There are stark and sustained differences in market outcomes between three- and four-player markets in Europe, and economic theory suggests these could be partly explained by the dynamic effects of competition on the ability and incentives to invest by market players. We find strong evidence that market concentration in Europe is below optimal levels that would maximise investments, especially in four-player markets. The dispersion of fixed costs and assets among a greater number of players can result in diseconomies of scale and a less efficient use of resources. We also find evidence that investment incentives to improve quality and innovate are lower in markets with lower concentration indices and profit margins.
Keywords: K20; L10; L40; L96; 330